Development of Self-Management Scale for Kidney Transplant Recipients, Including Management of Post-Transplantation Chronic Kidney Disease. (1st September 2013) - Kosaka, Shiho; Tanaka, Makoto; Sakai, Tomoko; Tomikawa, Shinji; Yoshida, Kazunari; Chikaraishi, Tatsuya; Kazuma, Keiko
Abstract : An evaluation scale is indispensable for the promotion of continuing, effective postkidney transplantation self-management behaviors. We aimed to develop and validate a new self-management scale for kidney transplant recipients to improve their long-term outcomes and prevent the recurrence of CKD complications. Two hundred and thirty-nine Japanese patients who had undergone kidney transplantation were recruited from three hospitals. The scale's validity and reliability were evaluated using exploratory factor analysis and intraclass correlation coefficients. Scale items were selected by considering the findings of a clinical importance survey of 17 experts. Four subscales were identified by the factor analysis: "Self-monitoring" (six items), "Self-care behavior in daily living" (seven items), "Early detecting and coping with abnormalities after kidney transplantation" (four items), and "Stress management" (three items). Cronbach's alpha coefficients for the subscales ranged from 0.61 to 0.87. A further four items with high clinical importance were added to the scale. The final scale comprised 24 items within four subscales and four single items. The intraclass correlation ranged from 0.88 to 0.95 in each subscale and the weighted kappa coefficient for the single items ranged from 0.33 to 0.72. The validity and reliability of our new self-management scale were confirmed by a patient-based field survey.